Systemic inflammation as a biomarker of seizure propensity and a target for treatment to reduce seizure propensity. Issue 1 (23rd January 2023) - Stredny, Coral; Rotenberg, Alexander; Leviton, Alan; Loddenkemper, Tobias
Abstract: People with diabetes can wear a device that measures blood glucose and delivers just the amount of insulin needed to return the glucose level to within bounds. Currently, people with epilepsy do not have access to an equivalent wearable device that measures a systemic indicator of an impending seizure and delivers a rapidly acting medication or other intervention (e.g., an electrical stimulus) to terminate or prevent a seizure. Given that seizure susceptibility is reliably increased in systemic inflammatory states, we propose a novel closed‐loop device where release of a fast‐acting therapy is governed by sensors that quantify the magnitude of systemic inflammation. Here, we review the evidence that patients with epilepsy have raised levels of systemic indicators of inflammation than controls, and that some anti‐inflammatory drugs have reduced seizure occurrence in animals and humans. We then consider the options of what might be incorporated into a responsive anti‐seizure system.